Coagulation tests and their association with postoperative blood loss after cardiac surgery with cardiopulmonary bypass - Ozolina, Agnese; Strike, Eva; Sondore, Antonina; Vanags, Indulis (Acta medica Lituanica, 2012)
Background. Platelet count (PLT), activated partial thromboplastin time (APTT), prothrombin time (PT) and fibrinogen are standard coagulation tests used for patients undergoing cardiac surgery with cardiopulmonary bypass (CPB). Materials and methods. 83 adult cardiac surgery patients were en rolled into a prospective study. Blood samples for APTT, PT, PLT, fibrino gen were collected preoperatively (T0), on admission to the intensive care unit (T1), 6 and 24 hours postoperatively (T6, T24). 24-hour postopera tive blood loss (24h-PBL) was registered. Results. The highest APTT mean value was 47  ±  13 sec at T6, in creasing from the baseline by 37%. The lowest mean value of PLT was 140 ± 47 × 109/L at T24, decreasing from the baseline by 32.5%. PT and fibrinogen mean values at all time points were within the normal range. Correlation with 24h-PBL was shown by T0 and T6 fibrinogen (r = –0.5, r  =  –0.4, P
Keywords: APTT; PT; PLT; fibrinogen; cardiac surgery